2013
DOI: 10.1002/jcc.23437
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modeling for Cu(II)‐aminopolycarboxylate complexes: Structures, conformational energies, and ligand binding affinities

Abstract: A ligand field molecular mechanics (LFMM) force field (FF) has been developed for d(9) copper(II) complexes of aminopolycarboxylate ligands. Training data were derived from density functional theory (DFT) geometry optimizations of 14 complexes comprising potentially hexadentate N2O4, tetrasubstituted ethylenediamine (ed), and propylenediamine cores with various combinations of acetate and propionate side arms. The FF was validated against 13 experimental structures from X-ray crystallography including hexadent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 57 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…Ligand field molecular mechanics (LFMM) was introduced by Deeth and co-workers, including explicit d-electron energy terms for transition metals to the standard MM expression 38,39 . This has previously been used to study small 40,41 and large metal-biomolecular systems such as metalloproteins 42,43 , including a range of transition metals such as Cu and Pt [44][45][46][47][48][49] . Recently, our group showed that LFMM is suitable for predicting geometries and exploring the conformational space of transition-metals such as Cu(II) and Pt(II) when bound to amyloid-β peptide, although we found this method fails to reproduce DFT energy 44 .…”
Section: Figure 1: Ghk Structurementioning
confidence: 99%
“…Ligand field molecular mechanics (LFMM) was introduced by Deeth and co-workers, including explicit d-electron energy terms for transition metals to the standard MM expression 38,39 . This has previously been used to study small 40,41 and large metal-biomolecular systems such as metalloproteins 42,43 , including a range of transition metals such as Cu and Pt [44][45][46][47][48][49] . Recently, our group showed that LFMM is suitable for predicting geometries and exploring the conformational space of transition-metals such as Cu(II) and Pt(II) when bound to amyloid-β peptide, although we found this method fails to reproduce DFT energy 44 .…”
Section: Figure 1: Ghk Structurementioning
confidence: 99%
“…In our work deriving accurate FFs targeted at specific transition-metal/ligand combinations, we have used both experimental and/or quantum chemical data [ 27 35 ]. Here, we focus on a particular class of flexible MOFs which incorporate the four-bladed zinc paddlewheel (ZPW) motif and construct a new, specialized valence FF, ZPW-FF, based on molecular ZPW complexes which then automatically captures the types of structural change displayed by [Zn 2 (bdc) 2 (dabco)] n as a function of adsorbate.…”
Section: Introductionmentioning
confidence: 99%